2007
DOI: 10.2147/cia.s798
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estrogens on skin aging and the potential role of SERMs

Abstract: Abstract:In humans, structural and functional changes attributable to aging are more visibly evident in the skin than in any other organ. Estrogens have signifi cant effects on skin physiology and modulate epidermal keratinocytes, dermal fi broblasts and melanocytes, in addition to skin appendages including the hair follicle and the sebaceous gland. Importantly, skin aging can be signifi cantly delayed by the administration of estrogen. This paper reviews the effects of estrogens on skin and the mechanisms by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(42 citation statements)
references
References 140 publications
0
31
0
1
Order By: Relevance
“…Further, the analysis of skin atrophy induced by chronic topical FA showed higher sensitivity of female mice to atrophic effects of lower FA doses. This was rather unexpected in view of protective anti-atrophic effects of estrogen in naturally aging skin mostly studied in postmenopausal women [19,33].…”
Section: Discussionmentioning
confidence: 98%
“…Further, the analysis of skin atrophy induced by chronic topical FA showed higher sensitivity of female mice to atrophic effects of lower FA doses. This was rather unexpected in view of protective anti-atrophic effects of estrogen in naturally aging skin mostly studied in postmenopausal women [19,33].…”
Section: Discussionmentioning
confidence: 98%
“…In particular, TNF-α is elevated in humans that are predisposed to chronic wounds and has been identified as a therapeutic target for impaired wound healing in the elderly (Ashcroft et al, 2012[ 13 ]). Both systemic and topical estrogen treatments enhance wound healing in elderly men and women by stimulating re-epithelialization, angiogenesis, matrix deposition and wound contraction whilst dampening the inflammatory response and expression of pro-inflammatory cytokines and proteolytic mediators (Ashcroft et al, 1997[ 8 ]; Ashcroft and Ashworth, 2003[ 7 ]; Thornton, 2013[ 145 ]; Archer, 2012[ 5 ]; Stevenson and Thornton, 2007[ 136 ]).…”
Section: Estrogen and Wound Healingmentioning
confidence: 99%
“…Scientific studies have shown the positive effects of estrogen skin on regeneration. It also decreases the aging process [32,33]. However, the use of such compounds has been banned because they caused too many side effects, unlike their plant counterparts [34].…”
Section: Phytohormonesmentioning
confidence: 99%